Factors that contribute to low bone density in postmenopausal women in different Amazonian communities - Borba-Pinheiro, Cláudio Joaquim [UNESP]; Drigo, Alexandre Janotta [UNESP]; Carvalho, Mauro César Gurgel de Alencar; Silva, Nádia Souza Lima da; Dantas, Estélio Henrique Martin (SAGE Publications, 2011)
Background: The aim of this study was to verify socioeconomic differences, nutrition, body balance and quality of life (QoL) in postmenopausal women with low bone mineral density (BMD) in two Amazonian communities. Methods: A total of 42 female volunteers participated in the study. The volunteers were separated into two groups: Villa (n= 20; 53±5.5 years) and City (n= 22; 56±7.9 years). The following evaluation instruments were used: dual energy X-ray absorptiometry (DXA); a socioeconomic questionnaire; a QoL questionnaire; a dietary habits questionnaire; and a balance test. Parametric and nonparametric tests were used. Results: The data showed significant differences in socioeconomic level (Δ%=+15.9%, p=0.000),lumbar spine L2-L4 (Δ%=+0.10%,p=0.007), balance(Δ%=+4.3%,p=0.03)and some important aspects of nutrition, such as the consumption of milk (Δ%=+34%, p=0.01) and alcohol (+14.8%, p=0.0001). These significant differences also contributed to the total QoL score (Δ%=+76.2%, p=0.000) and the majority of the QoL-related functions. Conclusion: This study verified that socioeconomic level, nutritional status, physical activity levels and QoL can influence the BMD of postmenopausal women. The study suggests new strategies for official health organizations to use in order to prevent and treat osteoporosis. In addition, this study can provide an orientation to physical activity, nutrition and medical professionals. © The Author(s), 2011.
Keywords: Bone density; Nutritional status; Postural balance; Quality of life; Socioeconomic level; adult; body equilibrium; bone density; Brazil; controlled study; cross-sectional study; dual energy X ray absorptiometry; feeding behavior; female; food intake; geographic distribution; health care organization; human; human experiment; lumbar spine; normal human; nutritional status; physical activity; postmenopause; prevalence; priority journal; quality of life; questionnaire; socioeconomics